Overexpression of plum auxin receptor PslTIR1 in tomato alters plant growth, fruit development and fruit shelf-life characteristics. Issue 1 (December 2016) - El-Sharkawy, I.; Sherif, S.; El Kayal, W.; Jones, B.; Li, Z.; Sullivan, A.; Jayasankar, Subramanian
Abstract Background TIR1-like proteins areF -box auxin receptors. Auxin binding to theF -box receptor proteins promotes the formation of SCFTIR1 ubiquitin ligase complex that targets the auxin repressors, Aux/IAAs, for degradation via the ubiquitin/26S proteasome pathway. The release of auxin response factors (ARFs) from their Aux/IAA partners allows ARFs to mediate auxin-responsive changes in downstream gene transcription. In an attempt to understand the potential role of auxin during fruit development, a plum auxin receptor, PslTIR1, has previously been characterized at the cellular, biochemical and molecular levels, but the biological significance of this protein is still lacking. In the present study, tomato (Solanum lycopersicum) was used as a model to investigate the phenotypic and molecular changes associated with the overexpression ofPslTIR1 . Results The findings of the present study highlighted the critical role ofPslTIR1 as positive regulator of auxin-signalling in coordinating the development of leaves and fruits. This was manifested by the entire leaf morphology of transgenic tomato plants compared to the wild-type compound leaf patterning. Moreover, transgenic plants produced parthenocarpic fruits, a characteristic property of auxin hypersensitivity. The autocatalytic ethylene production associated with the ripening of climacteric fruits was not significantly altered in transgenic tomato fruits. Nevertheless, the fruit shelf-life characteristics were affected by transgene presence, mainly through enhancing fruit softening rate. The short shelf-life of transgenic tomatoes was associated with dramatic upregulation of several genes encoding proteins involved in cell-wall degradation, which determine fruit softening and subsequent fruit shelf-life. Conclusions The present study sheds light into the involvement ofPslTIR1 in regulating leaf morphology, fruit development and fruit softening-associated ripening, but not autocatalytic ethylene production. The results demonstrate that auxin accelerates fruit softening independently of ethylene action and this is probably mediated through the upregulation of many cell-wall metabolism genes.